Inhibition and working memory of alpine skiers, soccer players and martial artists - Finkenzeller, T.; Hofer, A.; Amesberger, G. (Science and Skiing VII, 2018)
Inhibitory control of behavior, thoughts or emotions; adjusting to changed demands or priorities; and holding information in mind and mentally working with it typically reflect higher-order cognitive functions. These abilities are summarized in the concept of executive functions (EFs) consisting of inhibition, working memory, and cognitive flexibility (Diamond, 2013). In soccer, for instance, a player must adapt quickly to situational demands, make decisions, change strategies, and inhibit responses during a match (Vestberg et al., 2012). There is some empirical evidence that adolescent (Huijgen et al., 2015; Verburgh et al., 2014; Vestberg et al., 2017) and adult elite soccer players (Vestberg et al., 2012) are at a higher level in specific sub-domains of EFs than sub-elite players. Those results suggest that EFs are important for successful soccer performance. Cognitive processes are involved in every sport but with different demands on core EFs. It is expected that the requirements needed for different sports are reflected in specific patterns of EFs. This assumption is supported by a recent study of Jacobson and Matthaeus (2014), who showed differences in EFs of college students active in different sports. The authors speculate that sport is a kind of EFs training, and moreover, that the benefits of this training can be transferred to other non-sport situations. In accordance with Diamond (2013), a comprehensive EFs test battery was used in this study to assess information processing speed and capacity of working memory, as well as accuracy and speed of interference control. To detect sport-specific differences in EFs, adolescent soccer players, alpine skiers, and martial artists were compared. Thus, the aims of this study were to identify EFs patterns in adolescent athletes and to evaluate whether the EFs patterns are differently pronounced In adolescent alpine skiers, soccer players, and martial artists.